(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Organisations need to use cutting edge online marketing strategies to keep growing and increase sales in the e-commerce industry, which is always changing and very competitive. This paper looks at how customers’ habits have changed over time and how digital platforms have changed the way people shop online. It looks at how old ways of advertising, like markets and door-to-door sales, gave way to newer ones, like social media marketing, SEO, and SEM. The literature review lists the most important studies that show these strategies work to make people more aware of the brand and get more people to buy from people. A qualitative study is used to find out how important it is to use data analytics, personalise marketing strategies, and make user experiences better. The talk makes it clear how important it is to use good material, make online shopping easy, and run a business in a way that is fair and good for the environment. It also talks about the problems with data security and how customers’ demands are rising in the digital age. E-commerce companies can successfully handle the tricky digital market, reach more people around the world, and be successful in the long run by using an all-encompassing and unified online marketing strategy. At the end of the paper, it is emphasised how important it is to keep adapting and coming up with new ideas in order to stay successful in the ever-changing world of e-commerce.